Design of a class of generalized parallel mechanisms with large rotational angles and integrated end-effectors. (April 2019) - Jin, Xiaodong; Fang, Yuefa; Zhang, Dan
Highlights: A new method for structural synthesis of the generalized parallel mechanisms with large rotational angles and integrated end-effectors is presented. The proposed method provides a way to integrate the end-effectors into parallel mechanisms. The proposed method presents a way to design multi-dimension independent rotational DOF without restricting the translational DOF. A 3T3R generalized parallel mechanism with high rotational capability is obtained and a class of 4-DOF and 6-DOF generalized parallel mechanisms with integrated end-effectors is designed. The proposed mechanisms possess excellent motion performance and high task specificity. Abstract: The generalized parallel mechanisms (GPMs) become a new feasible research topic to explore the advantages and overcome the shortcomings of the traditional parallel mechanisms (TPMs). This paper aims to address the challenge of the synthesis method for the GPMs with large rotational angles and integrated end-effectors (or configurable platforms). A sufficient condition for the independent rotations is presented and a design framework for constructing independent rotational degree of freedom (DOF) is developed. Using the set mapping and the Lie group theory, a method for synthesizing GPMs with hybrid structures is proposed on the basis of the obtained sufficient condition and the design framework. This method provides a way to connect the symmetric 0-DOF closed-loop kinematic chains with the parallel limbs to preserve the motions of both the parallel limbs and the elements in the closed-loop chains. A 3T3R GPM with 3-dimension large rotational angles and a class of 4-DOF and 6-DOF GPMs with 1-DOF integrated end-effectors are synthesized using the proposed method. The orientation workspace of the example GPMs are analyzed and discussed to reveal the high rotational capability. The obtained GPMs are suitable for the occasions that require high rotational performance, assembly, pick-and-place, drilling and other industrial applications.